Tren penggunaan kecerdasan buatan dalam pembelajaran mahasiswa sarjana dan diploma Fakultas Ekonomi dan Bisnis Universitas Udayana - Cahyaningtyas, Dwi Fitrina (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2024)
Purpose. This study aims to explore the use of Chat AI and see the information search behavior patterns of students at the Faculty of Economics and Business, Udayana University. Methodology. This research was conducted by survey with descriptive. The respondents were diploma and undergraduate students from the Faculty of Economics at Udayana University. The questionnaire was distributed through WhatsApp groups by filling out a google form and open questions. Results and discussion. More than half of the students have utilized AI technology, particularly Chat AI, in their coursework to complete daily assignments. However, the information obtained through Chat AI is not yet fully trusted. Their information-seeking behavior tends to follow Ellis's model due to the relevance of the information to their needs. Conclusions. The ease of obtaining information and time efficiency offered by AI has created a trend among students in their learning process. However, limitations on AI usage are necessary to maintain the integrity of higher education.